Characteristics of firms electing early adoption of SFAS 52 - Ayres, Frances L. (Journal of Accounting and Economics, 1986)
In 1981 the FASB issued a new standard for accounting for foreign currency translation, SFAS 52. The standard provided a gradual transition period, allowing firms to select from several possible adoption dates. This study extends the research on the positive theory of accounting choice to examine the factors associated with a management's choice of adoption date. The comparison reveals that early adopters were smaller, typically decreased in pre-charge earnings the year before adoption, had less stock owned by directors and officers, and were more constrained on dividend payouts and interest coverage ratios than later adopters.